Narcissistic sexual predation: Keith Raniere’s grooming practices in NXIVM - Raine, Susan (My University, 2021)
The 2019 trial of NXIVM founder and leader, Keith Raniere, detailed various forms and aspects of his exploitative practices, including those of a sexual nature. In this article I address a particular component of the sexual abuse process: the grooming of women for sexual exploitation. Many of Raniere’s teachings and behaviors prepared—or groomed—female members of NXIVM for his increasingly coercive and humiliating sexual demands. In addition to forms of grooming directed through group teachings, Raniere also established personal relationships with numerous women, during which he groomed them on an individual basis. Using Grant Sinnamon’s (2017) research on the grooming of adults for sexual abuse, in conjunction with Janja Lalich’s (1997) work on the psychosexual exploitation of women in cults, I analyze the many ways that Raniere groomed women in NXIVM. Furthermore, I integrate Sinnamon’s (2017) specific observations regarding narcissistic sexual predators to explore Raniere’s probable narcissism and how this manifested in his grooming practices.
Keywords: NXIVM; Keith Raniere; exploitative practices; grooming; sexual abuse; sexual predation